Social and Economic Interventions to Alleviate Poverty in Makassar City: An Approach Using Human Capital Theory and Kurt Lewin's Change Model - Tamsah, Hasmin; Nurung, Jumiaty (Jurnal Manajemen Bisnis, 2024)
This study aims to identify factors influencing poverty in Makassar City and propose effective social and economic interventions based on Human Capital Theory and Kurt Lewin's Change Model. It utilizes a qualitative approach employing grounded theory methodology. Data collection involved observation, documentation, and in-depth interviews with 31 informants: government officials (2), poverty activists (3), and impoverished families (26) in Makassar City. NVivo software facilitated data analysis to determine key criteria and relationships among these factors. The study highlights poor sanitation quality, low education levels, limited motivation to escape poverty, and reliance on government aid as primary poverty exacerbators in Makassar. Proposed interventions include enhancing sanitation infrastructure, educational initiatives, skill development, and fostering social networks. These findings underscore the importance of an integrated approach to poverty alleviation. Theoretically, the study supports Human Capital Theory by emphasizing investment in education, skills, and health to boost productivity and community welfare. Managerially, the government is urged to implement programs improving sanitation, education access, economic empowerment, and ensure ongoing effectiveness through continuous monitoring.